Rational Antibiotic Therapy of Respiratory Tract Diseases in Сhildren - S.O. Kramariev (Zaslavsky O.Yu., 2016)
The prevalence of bacterial infections of the respiratory tract, especially in children, the presence of complications that threaten the health and lives of patients necessitate the administration of a rational systemic antibiotic therapy. As the first-line drug in respiratory infections, it is recommended to use amoxicillin, the second one - amoxicillin clavulanate. In the case of community-acquired atypical pneumonia, azithromycin should be administered.